2020
DOI: 10.1007/s00338-020-01959-x
|View full text |Cite
|
Sign up to set email alerts
|

Sub-annual fluorescence measurements of coral skeleton: relationship between skeletal luminescence and terrestrial humic-like substances

Abstract: Some massive coral core slices reveal luminescent bands under ultraviolet light, which have been attributed to terrestrial humic acids in the skeleton. Coral luminescence has therefore been used to reconstruct past climate and hydrological variability. However, it has remained unresolved how closely coral luminescence at sub-annual resolution is related to terrestrial humic acid concentrations. This study presents a solution-based fluorescence method to quantify terrestrial humic substances in less than 4 mg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Future research needs to corroborate our estimate by reconstructing past variation in terrigenous CDOM in this re gion, e.g. using luminescence data from coral skele ton cores as a terrigenous CDOM palaeo-proxy (Kaushal et al 2020(Kaushal et al , 2021. Nevertheless, our study already indicates that the disturbance of tropical peatlands has likely resulted in CDOM-mediated coastal browning in Southeast Asia, and that peatland disturbance therefore entails an additional environmental impact beyond the large increases in CO 2 emissions from peat and peatland DOC oxidation (Hooijer et al 2010, Murdiyarso et al 2010, Wit et al 2018.…”
Section: Impact Of Terrigenous Cdom On Light Availabilitymentioning
confidence: 98%
“…Future research needs to corroborate our estimate by reconstructing past variation in terrigenous CDOM in this re gion, e.g. using luminescence data from coral skele ton cores as a terrigenous CDOM palaeo-proxy (Kaushal et al 2020(Kaushal et al , 2021. Nevertheless, our study already indicates that the disturbance of tropical peatlands has likely resulted in CDOM-mediated coastal browning in Southeast Asia, and that peatland disturbance therefore entails an additional environmental impact beyond the large increases in CO 2 emissions from peat and peatland DOC oxidation (Hooijer et al 2010, Murdiyarso et al 2010, Wit et al 2018.…”
Section: Impact Of Terrigenous Cdom On Light Availabilitymentioning
confidence: 98%
“…Consequently, we may probably consider the humic-like material as a good tracer of sand groundwater (SL), and more generally of stagnant and/or superficial freshwaters, such as HR and 3BR. Interestingly, Kaushal et al (2020) have shown that this (terrestrial) humic-like material was readily incorporated in coral skeletons, suggesting that coral cores may have the potential to reconstruct past variations in freshwater fluxes.…”
Section: Freshwaters Impacting Reef Watersmentioning
confidence: 99%
“…Our estimate of the anthropogenic contribution to the observed CDOM-mediated light attenuation relies on earlier reports that the peatland tDOC flux has increased by slightly over 50% as a result of land conversion (Moore et al 2013, Yupi et al 2016). Future research should therefore aim to corroborate our estimate by reconstructing past variation in terrigenous CDOM in this region, which may become possible through measurements of humic acid concentrations in coral skeleton cores (Kaushal et al 2020). Nevertheless, our study already indicates that the disturbance of tropical peatlands has likely resulted in CDOM-mediated coastal browning in Southeast Asia, and that peatland disturbance therefore entails an additional environmental impact beyond the large increases in CO2 emissions from peat and peatland DOC oxidation (Hooijer et al 2010, Murdiyarso et al 2010, Wit et al 2018.…”
Section: Impact Of Terrigenous Cdom On Light Availabilitymentioning
confidence: 62%